Comparison of Administration Routes on the Protective Effects of Bee Venom Phospholipase A2 in a Mouse Model of Parkinson’s Disease - Baek, Hyunjung; Jang, Hyun Il; Jeon, Hat Nim; Bae, Hyunsu (Frontiers in Aging Neuroscience, 2018)
Parkinson’s disease (PD) is the second most common neurodegenerative disorder worldwide. Progressive loss of dopaminergic neurons in the substantia nigra (SN) and their synaptic terminal connections in the striatum are main characterizations of PD. Although many efforts have been made to develop therapeutics, no treatment has been proven effective. We previously demonstrated that bvPLA2 can protect dopaminergic neurons by modulating neuroinflammatory responses in an MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine)-induced mouse model of PD. The cellular basis for the neuroprotective response of bvPLA2 was the induction of CD4+CD25+ regulatory T cells (Tregs), a population known to suppress immune activation and maintain homeostasis and tolerance to self-antigen. The aim of the present study was to investigate the effects of different routes of bvPLA2 administration in a PD mouse model. Neurobehavioral assessment revealed progressive deterioration in locomotor functions of the MPTP group compared with the control group. However, such functions were improved following subcutaneous (s.c.) bvPLA2 administration. The results showed that the s.c. route of bvPLA2 administration contributed to the induction of Treg cells and the reduction of Th1 and Th17 populations, demonstrating that the neuroprotective effects were associated with reduced tyrosine hydroxylase (TH)-positive dopaminergic neurons and microglia. These results suggested that the s.c. bvPLA2 injection could be beneficial for treating aspects of PD.